2020
DOI: 10.1101/2020.07.08.180869
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The everyday acoustic environment and its association with human heart rate: evidence from real-world data logging with hearing aids and wearables

Abstract: Prolonged acoustic noise negatively affects human cardiovascular health. However, noise is typically defined by acoustic intensity (i.e. pressure levels) alone, which neglect other dimensions of the sound associated with e.g. the ease of listening. In this study, we used in-market data from hearing aid users to investigate the longitudinal association between multidimensional characteristics of everyday sound logged by the hearing aids and continuous mean heart rate measures logged by the user's own we… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Specifically, the study by Christensen et al (2021) found that higher ambient sound pressure levels were associated with increases in HR, while El Aarbaoui et al (2017) further documented that higher sound pressure levels also relate to decreases in HR variability. Moreover, increases in ambient signal-to-noise ratio were linked to decreases in HR, particularly in noisy environments (Christensen et al, 2021).…”
Section: Introduction/backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…Specifically, the study by Christensen et al (2021) found that higher ambient sound pressure levels were associated with increases in HR, while El Aarbaoui et al (2017) further documented that higher sound pressure levels also relate to decreases in HR variability. Moreover, increases in ambient signal-to-noise ratio were linked to decreases in HR, particularly in noisy environments (Christensen et al, 2021).…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…Specifically, the study by Christensen et al (2021) found that higher ambient sound pressure levels were associated with increases in HR, while El Aarbaoui et al (2017) further documented that higher sound pressure levels also relate to decreases in HR variability. Moreover, increases in ambient signal-to-noise ratio were linked to decreases in HR, particularly in noisy environments (Christensen et al, 2021). In their respective studies, Christensen et al (2021) used hearing aids and wrist-worn wearables to collect real-world environmental sound and HR data, while El Aarbaoui et al ( 2017) had participants wear shoulder-mounted noise dosimeters and medical-grade heart-rate monitoring devices.…”
Section: Introduction/backgroundmentioning
confidence: 99%
See 3 more Smart Citations